What's new Scooby-Doo. Volume 3 : Halloween boos and clues [videorecording (DVD)] - Kasem, Casey; Welker, Frank; Cohn, Mindy, 1966-; DeLisle, Grey; Awley, Scott; Smith, Dexter (What's new Scooby-Doo?, 2004)
Vampire strikes back: The gang runs into a real life vampire in a Transylvanian castle. Mummy scares best: The gang investigates a mummy on the loose in Egypt. High-tech house of the future: The gang is trapped in a beserk automated house of the future at the Omaha World Fair. She sees a sea monster by the sea shore: The gang's tropical island vacation is ruined by a boat-smashing sea monster.